Policy Constraints and Key Drivers for Enhancing Egyptian Agrifood Systems - Salem, Shaban Ali; Dhehibi, Boubaker; M. Oumer, Ali; Abd-Allah, Emman; Souissi, Asma; Akramov, Kamiljon; Baum, Michael (International Center for Agricultural Research in the Dry Areas, 2023)
Food security is one of the most important strategic issues for all countries, as it represents an integral part of their national security. For this purpose, all countries all over the world aim to achieve food security for their citizens to ensure the political independence and well-being of their citizens. In this framework, food security has been one of the most important issues for the Egyptian government following the revolution on the 25th of January 2011, since one of the basic demands of the revolution was achieving food security for Egyptian citizens under the slogan “Bread - Freedom - Social justice”, and the achievement of the dignity of humanity. Therefore, the issue of food security represents a fundamental pillar in the Egyptian economy due to its close connection to the process of economic development on the one hand, and political and social stability on the other hand.